Bacteria-induced intracellular signalling in platelets. (June 2015) - McNicol, Archie
Abstract Multiple studies have now shown that various species of bacteria can stimulate platelets; many in a strain and donor-dependent manner. The signalling pathways underlying this platelet activation has been the subject of scrutiny for the last decade. The best-delineated pathway is that in response to Streptococcal species, such as Streptococcus sanguinis (S. sanguinis), Streptococcus gordonii (S. gordonii) and Streptococcus oralis (S. oralis), where a pathway is initiated by the engagement of the low affinity IgG receptor, FcγRIIA. This leads to and involves the tyrosine kinase Syk, the adaptor protein Linker of Activated T Cells (LAT) and subsequently both phospholipase Cγ2 (PLCγ2) and phosphatidylinositol-3-kinase (PI-3-K). Finally, this leads to the expression of the αIIbβ3 integrin, the synthesis and release of thromboxane A2 (T × A2) and the exocytosis of PF4, each of which plays a crucial role in secondary signalling and full platelet activation. Roles for other signalling pathways in Streptococcal-induced platelet activation are less clear, although an ADP-mediated inhibition of adenylyl cyclase, a glycoprotein Ib/IX/V-mediated pathway and perhaps a complement-induced pathway have each been proposed. Platelet activation by Porphyromonas gingivalis (P. gingivalis) at least partially shares the FcγRIIA/Syk/PLCγ2/PI-3-K mechanism utilised by Streptococcal species. However, it has also been suggested that P. gingivalis activates platelets by two additional methods; stimulation of the protease-activated receptors leading to activation of phospholipase Cβ (PLCβ), and the engagement of Toll-like receptors 2 and 4 by released lipopolysaccharide leading to an ill-defined pathway which may involve PI-3-K. Consequently, it appears that bacteria can stimulate platelets by eliciting multiple signalling pathways some of which are common, and some unique, to individual species.